The Ethics of Social Media Communication in the Perspective of the Al-Qur’an - Wati, Desy Rahma (Journal of Islamic Communication and Counseling, 2023)
This article will discuss the ethics of social media communication which is becoming a concern in the world. There is much negative news that is raised both in groups and individually. Reporting or account accounts on social media that are used not to attack each other in the form of provocation, forming opinions that cause defamation, sending pornographic content, and so on. This writing method uses Library Research by referring to several primary and secondary sources, namely the Qur'an, books, and journals. From this research, it is said that being a Muslim when communicating on social media is very dangerous if it is not accompanied by the right communication ethics, especially on social media. The rules in the Qur'an become a guide for Muslims to implement the correct and beneficial application.